An optimised handover mechanism for VANETS - Danish Ather,Raghuraj Singh, Ravi S Shukla (International Journal of Advanced Science and Technology, 2020)
“Mobile ad-hoc network has a subcategory defined as “Vehicular ad-hoc network” and these network have the only difference of moving vehicles as nodes. In the current scenario, the pace of growth of VANET is extremely high. The two primary components of network are self-organized along with VANET’s component. In VANET, vehicles are able to share information or data & do not need infrastructure for communication along with other earlier required vehicles as well as “roadside units (RSU)”. The types of networks experience topology which is extremely dynamic is having frequent disconnection attributes and having fast-moving vehicles. An effective routing algorithm is required for handover management.